Involvement of the Tetraspanin 2 (TSPAN2) Gene in Migraine: A Case-Control Study in Han Chinese - Fang, Jie; Yuan, Xiaodong; An, Xingkai; Qu, Hongli; Wang, Chen; Hong, Ganji; Zheng, Liangcheng; Yi, Kehui; Chen, Shuai; Wang, Xinrui; Ma, Qilin (Frontiers in Neurology, 2018)
Tetraspanin 2 (TSPAN2) belongs to the tetraspanin superfamily. Previous studies identified significant associations of TSPAN2 SNPs rs12134493 and rs2078371 with migraine in Western populations; however, these associations need to be confirmed in the Chinese Han population. In addition, we studied whether TSPAN2 is associated with susceptibility to migraine to provide a new clinical evidence. A case-control study (425 patients with migraine and 425 healthy controls) in a Chinese Han population was performed to evaluate the associations between migraine and TSPAN2 via a genotype-phenotype analysis between TSPAN2 and clinical symptoms. SNP rs2078371 was significantly associated with migraine in recent studies, especially in migraine without aura (MO) and female patients. Meta-analysis revealed that the A allele of rs12134493 was significantly associated with migraine (OR = 1.14, P = 0.0001). Our findings suggested that TSPAN2 is a potential susceptibility factor for migraine. To confirm our results, a large-scale Chinese Han population study should be conducted. Considering that these two SNPs have not been definitively shown to affect TSPAN2 or regulate nearby genes in this genomic region, the biological function and molecular mechanism of TSPAN2 in migraine should be further explored.